(untitled) (Medico Legal Update, 2020)
The present study aimed to investigate the histological, enzyme histochemical changes and liver function effects of Maxxthor insecticide on albino rats in liver. The experiment included 20 rat which were divided into four groups, the first group 5 rats were considered the control animals and the others were divided equally into three groups with a dose of 0.01, 0.1and 1 mg / kg of body weight, respectively for a period 40 days. The animals given each 48 hours via oral route Maxxthor by tube dosage after dissolved with distilled water. Microscopic examination of liver showed inflammatory cell aggregation around vessels, congestion and dilation of sinusoids hepatocytes hypertrophy with severs inflammatory cells infiltration, kupffer cells proliferation and hydropic degeneration. Enzyme histochemical study of liver showed weak expression of ALP activity in hepatocyte in low dose, sever expression in middle dose, and mild expression in high dose. There was significantly increase in serum aminotransferases (ALT, AST) and alkaline phosphatase (ALP) level in treated group of rats as compared with control group.